2003
DOI: 10.1002/ejoc.200200618
|View full text |Cite
|
Sign up to set email alerts
|

The Substituent Effect of the Phosphaalkenyl Group

Abstract: Several novel phosphaalkenes (E)-Mes*P=CHC 6 H 4 X (6; X = Me 3 Si, Me 3 Sn, CHO, COOH, CN) were prepared and, together with other known members of this series, subjected to an analysis of linear free-energy relationships based on the values of pK a and values of δ( 13 C para ) of substituted benzoic acids and on the values of δ( 13 C para ) of substituted bromobenzenes. These analyses indicate that the (E)-Mes*P=CH group is a weak electron donor with a predominantly inductive effect (σ p = −0.1) on a neighbor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 27 publications
(22 reference statements)
1
16
0
Order By: Relevance
“…The ancillary ligands Et 3 P, Et 2 PPh, and EtPPh 2 were chosen to provide a certain variability in the donor properties and to maximize the chance of obtaining a crystalline product for concise characterization. Taking into account the results of Lammertsma and co-workers [19][20][21] on the synthesis of nucleophilic ruthenium phosphinidene complexes, [22,23] we expected to obtain the terminal phosphinidene complexes [(η 6 -C 6 H 6 )(PR 3 )Ru(η 1 -P-PtBu 2 )] or the related side-on complexes [(η 6 -C 6 H 6 )(PR 3 )Ru(η 2 -P=PtBu 2 )]. To our surprise, we found that the reaction takes a more complicated and unexpected pathway, yielding products with completely different molecular structures, the characterizations of which are reported below.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The ancillary ligands Et 3 P, Et 2 PPh, and EtPPh 2 were chosen to provide a certain variability in the donor properties and to maximize the chance of obtaining a crystalline product for concise characterization. Taking into account the results of Lammertsma and co-workers [19][20][21] on the synthesis of nucleophilic ruthenium phosphinidene complexes, [22,23] we expected to obtain the terminal phosphinidene complexes [(η 6 -C 6 H 6 )(PR 3 )Ru(η 1 -P-PtBu 2 )] or the related side-on complexes [(η 6 -C 6 H 6 )(PR 3 )Ru(η 2 -P=PtBu 2 )]. To our surprise, we found that the reaction takes a more complicated and unexpected pathway, yielding products with completely different molecular structures, the characterizations of which are reported below.…”
Section: Resultsmentioning
confidence: 99%
“…[51] The most striking difference between the X-ray structures of 1b and 1c and those previously reported is a significantly increased distance between the η 5 -dienyl unit and the Ru [centroid C2C3C4C5C6-Ru1 in 1b, 1.728(2) Å] compared with in, for example, [(η 5 -C 6 H 7 )Ru(L)] + [L = N-methyl-N,N′-bis(2-pyridylmethyl)amine, 1.668 Å], [57] which indicates that the bonding of the cyclohexadienyl skeleton to ruthenium in 1b and 1c is weaker than in previously reported structures with auxiliary tridentate chelate N ligands. (19), Ru1-C2 2.267(2), Ru1-C3 2.197 (7), Ru1-C4 2.202 (7), Ru1-C5 2.148 (7), Ru1-C6 2.215(7), C1-C2 1.519(10), C2-C3 1.398(10), C3-C4 1.422(10), C4-C5 1.425(10), C5-C6 1.435(11), C6-C1 1.508(10), C1-P3 1.932 (7), P3-P4 2.201(3), P3-Si1 2.285 (7), center of centroid (Cc) C2C3C4C5C6-Ru1 1.728(2), P1-Ru1-P2 95.46 (7), P1-Ru1-Cl1 89.28(9), P2-Ru1-Cl1 90.18 (7), Cc-Ru1-P1 123.90 (7), Cc-Ru1-P2 127.60, Cc-Ru1-Cl1 120.03 (6).…”
Section: X-ray Structural Analysismentioning
confidence: 99%
“…In this respect, the P¼C bond is remarkably similar to the C¼C bond. 683 Experimental and theoretical studies on the conjugation of the P¼C bond with a cyclopropyl group also indicate great similarity between P¼C and C¼C bonds. 684 Further studies of the reactivity of the phosphaalkenes RP¼C(NMe 2 ) 2 , having inverted polarisation of the P¼C bond, have also appeared.…”
Section: P P -Bonded Phosphorus Compoundsmentioning
confidence: 99%
“…9 It is favorable if dispersants contain the surfactant molecules having both pigment-and solvent-affinity ends. [13][14][15] Polymeric pigment dispersants are copolymers with pigment affinic "anchoring group" and soluble polymeric chains "stabilizing group". [16][17][18][19] In the case of polymeric dispersants, however, dispersion stabilization is generally provided by two major mechanisms: electrostatic and steric stabilization.…”
Section: Introductionmentioning
confidence: 99%